Constraint Analysis of Paddy Promotion Programmes under Decentralized Planning - Seby, Salpriya; M.J., Mercykutty; R, Sendilkumar (Journal of Extension Education, 2019)
A study was conducted in Thrissur district of Kerala, with the objective to find out the constraints felt by the beneficiary farmers and extension personnel while implementing of paddy promotion programmes under decentralized planning. Ex-post facto research design was employed and multi-stage sampling method was followed. Thirty farmers, each identified from three gramapanchayats viz;Adat, Arimpur and Chelakkara and 30 extension personnel representing 3 blocks of Thrissur district were surveyed. Analysis was carried out using Kruskal Wallis test. The dimension wise constraints perceived indicates that financial, time, infrastructural, knowledge, market and scheme feature were the most severe, followed by manpower and input constraints as more severe in Arimpur panchayat. The major constraints perceived by the extension personnel were manpower constraints, financial, scheme feature, input, time and infrastructural constraints, in that order.